Enterprise characteristics of geese farming in selected areas of Oyo state in the tropical region of Nigeria - OLUBISI, EWUOLA EMMANUEL; ODUNAYO, AKINBOLAGBE OLUWAFEMI; TOLUWANI, AKINBOLA ELIZABETH (The Indian Journal of Animal Sciences, 2025)
Geese enterprise in most tropical countries is still at the rudimentary stage. Yet, if produced on a large scale, geese production could bring maximum profit. This study focused on providing detailed information on the enterprise characteristics of geese farming in Oyo State, Nigeria. Quantitative data were collected using semi-structured questionnaires. Geese farmers across selected local government area in Oyo State were interviewed. A descriptive cross-sectional design was used for this study. Some of the geese farmers had been involved in geese production for about five 5 years. Many of them solely engaged in the geese production to sell them while not too many (39%) engaged in geese production to sell and consume them. Many of the geese farmers (59.3%) reported that they adopted the free-range production system while some of the farmers (32.2%) used the deep litter production system, while few of them (8.5%) raised their geese in cages. Most of the geese farmers (71.2%) reported they got their foundation stock from commercial hatcheries. Many farmers reported that they produced geese eggs to sell the hatchling and their eggs hatched naturally. Also, some farmers reported that they fed their geese using formulated feeds. It was concluded from this study that geese are mostly reared on free range and fed with formulated feed and the hatchings of their egg is usually by natural brooding in Oyo State, Nigeria. However, geese farmers must be more aware of modern ways of geese production and adoption. Also, the scientific management practices including all technical aspects of geese production like breeding, feeding and housing must be enhanced.